2014
DOI: 10.1016/j.cell.2014.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Dynamics of Enhanceosome Assembly in Embryonic Stem Cells

Abstract: Enhancer-binding pluripotency regulators (Sox2 and Oct4) play a seminal role in embryonic stem (ES) cellspecific gene regulation. Here, we combine in vivo and in vitro single-molecule imaging, transcription factor (TF) mutagenesis, and ChIP-exo mapping to determine how TFs dynamically search for and assemble on their cognate DNA target sites. We find that enhanceosome assembly is hierarchically ordered with kinetically favored Sox2 engaging the target DNA first, followed by assisted binding of Oct4. Sox2/Oct4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
783
6
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 575 publications
(842 citation statements)
references
References 46 publications
51
783
6
2
Order By: Relevance
“…Interestingly, at an earlier time point (48 h postinfection), SOX2 ChIP signal on Klf4 and Nanog enhancers was equal to uninfected cells, if not higher, indicating that at these loci OCT4 depletion is initially compensated by an increase in SOX2 binding. This result is not unreasonable, given that both OCT4 and SOX2 were shown to independently bind to the O/S composite motif (26) and that singlemolecule imaging indicates that SOX2 engages the target DNA first, followed by OCT4 (27). Most importantly, when we checked SCC chromatin binding in OCT4-depleted cells using RAD23B antibody, we observed that it closely followed SOX2 kinetics at all tested loci, reaching background levels 72 h post OCT4 depletion (Fig.…”
Section: Rad23b Targets Gene Promoters and Distal Regulatory Regions Inmentioning
confidence: 87%
“…Interestingly, at an earlier time point (48 h postinfection), SOX2 ChIP signal on Klf4 and Nanog enhancers was equal to uninfected cells, if not higher, indicating that at these loci OCT4 depletion is initially compensated by an increase in SOX2 binding. This result is not unreasonable, given that both OCT4 and SOX2 were shown to independently bind to the O/S composite motif (26) and that singlemolecule imaging indicates that SOX2 engages the target DNA first, followed by OCT4 (27). Most importantly, when we checked SCC chromatin binding in OCT4-depleted cells using RAD23B antibody, we observed that it closely followed SOX2 kinetics at all tested loci, reaching background levels 72 h post OCT4 depletion (Fig.…”
Section: Rad23b Targets Gene Promoters and Distal Regulatory Regions Inmentioning
confidence: 87%
“…Previous single-molecule studies of TFs have consistently found two populations in the survival probability distributions: a short-lived population with RTs on the order of hundreds of milliseconds and a longer-lived population with RTs on the order of tens of seconds to minutes (Chen et al 2014b;Normanno et al 2015;Hansen et al 2017). These two populations have often been shown to be the nonspecific and specific binding populations, respectively.…”
Section: Single-molecule Imaging In Living Drosophila Embryos Using Llsmmentioning
confidence: 99%
“…To further validate our observation that the RT of the long-lived population of BCD is highly transient compared with the 10-60 sec typically observed for other sequence-specific DNA-binding TFs using single-molecule tracking (Chen et al 2014b;Hansen et al 2017), we performed fluorescence recovery after photobleaching (FRAP) experiments on BCD in the embryo (Fig. 1D), which revealed halftimes of BCD recovery on the order of hundreds of milliseconds (Supplemental Fig.…”
Section: Single-molecule Imaging In Living Drosophila Embryos Using Llsmmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, single-molecule fluorescence microscopy has been used to study TF localization in living cells across a range of model organisms, including bacteria, yeast and multi-cellular organisms [1016]. Many studies suggest complexities in diffusion and binding [4,11,12,15,17] which may include intersegmental transfer [4,11,17]. However, until now, the direct experimental evidence for intersegmental transfer has been limited.…”
Section: Introductionmentioning
confidence: 99%